2015
DOI: 10.1111/ijpp.12218
|View full text |Cite
|
Sign up to set email alerts
|

Employing the nominal group technique to explore the views of pharmacists, pharmacy assistants and women on community pharmacy weight management services and educational resources†

Abstract: Pharmacists, pharmacy assistants and women feel that community pharmacies have a definite role to play in weight management. Pharmacy-specific weight management educational resources that are readily available to pharmacy staff and women are highly desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Nonetheless, pharmacists’ and GPs’ attitudes towards extended services in this review reflected international findings, where pharmacists in North America, Asia, Australasia, South America and Europe were also enthusiastic towards the concept of providing extended services (Dosea et al., ; Fang, Yang, Feng, Ni, & Zhang, ; Kinsey, Scahill, Bye, & Harrison, ; Kjome, Sandberg, & Granas, ; Schindel et al., ). Moreover, lack of awareness (Bjorkman, Viberg, Rydberg, & Stalsby Lundborg, ; Fakih, Marriott, & Hussainy, ; Freeman, Cottrell, Kyle, Williams, & Nissen, ; Wibowo, Sunderland, & Hughes, ), issues with community pharmacy premises (Babiker, Carson, & Awaisu, ; Bjorkman et al., ; Donald et al., ; Gray, Chamberlain, & Morris, ; Hattingh, Emmerton, Ng Cheong Tin, & Green, ; Murphy et al., ), lack of management support (Casserlie & Mager, ; Donald et al., ; Kinsey et al., ; Tsao et al., ; Watkins, McKee, Hughes, & Pfeiffenberger, ) and remuneration (Donald et al., ; Gray et al., ; Kinsey et al., ; Watkins et al., ) have also been found in other countries. Many pharmacists elsewhere also stressed the need for sufficient pharmacy staff (Casserlie & Mager, ; Gray et al., ; Kinsey et al., ; Murphy et al., ; Tsao et al., ), and pharmacists’(Donald et al., ; Jorgenson, Laubscher, Lyons, & Palmer, ; Watkins et al., ; Wibowo et al., ) and GPs’ (Bryant, Coster, Gamble, & McCormick, ; Dhillon et al., ; Tan, Stewart, Elliott, & George, ) views confirmed poor engagement between pharmacists and GPs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, pharmacists’ and GPs’ attitudes towards extended services in this review reflected international findings, where pharmacists in North America, Asia, Australasia, South America and Europe were also enthusiastic towards the concept of providing extended services (Dosea et al., ; Fang, Yang, Feng, Ni, & Zhang, ; Kinsey, Scahill, Bye, & Harrison, ; Kjome, Sandberg, & Granas, ; Schindel et al., ). Moreover, lack of awareness (Bjorkman, Viberg, Rydberg, & Stalsby Lundborg, ; Fakih, Marriott, & Hussainy, ; Freeman, Cottrell, Kyle, Williams, & Nissen, ; Wibowo, Sunderland, & Hughes, ), issues with community pharmacy premises (Babiker, Carson, & Awaisu, ; Bjorkman et al., ; Donald et al., ; Gray, Chamberlain, & Morris, ; Hattingh, Emmerton, Ng Cheong Tin, & Green, ; Murphy et al., ), lack of management support (Casserlie & Mager, ; Donald et al., ; Kinsey et al., ; Tsao et al., ; Watkins, McKee, Hughes, & Pfeiffenberger, ) and remuneration (Donald et al., ; Gray et al., ; Kinsey et al., ; Watkins et al., ) have also been found in other countries. Many pharmacists elsewhere also stressed the need for sufficient pharmacy staff (Casserlie & Mager, ; Gray et al., ; Kinsey et al., ; Murphy et al., ; Tsao et al., ), and pharmacists’(Donald et al., ; Jorgenson, Laubscher, Lyons, & Palmer, ; Watkins et al., ; Wibowo et al., ) and GPs’ (Bryant, Coster, Gamble, & McCormick, ; Dhillon et al., ; Tan, Stewart, Elliott, & George, ) views confirmed poor engagement between pharmacists and GPs.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, previous research has reported that modest weight loss (3–5 kg), such as that achieved in this scoping review, can improve surrogate markers of cardiovascular disease . Moreover, studies examining the perceptions of patients, obesity experts and pharmacists and other pharmacy team members revealed a positive perception of pharmacists’ role in weight and obesity management …”
Section: Discussionmentioning
confidence: 99%
“…18 This process has been shown to be a valid methodology to achieve consensus of participants in healthcare research, including research of opinions regarding community pharmacy. [19][20][21] The 12 participants in two focus groups were registered pharmacists recruited using notices in newsletters of professional organisations. The participants included seven pharmacists working in community practice, two pharmacists working in hospital practice, two pharmacists performing medication reviews (a further three pharmacists were credentialed to do reviews) and one pharmacist working as a practice development pharmacist with a professional association.…”
Section: Confirmation Of the Environmental Frameworkmentioning
confidence: 99%